KARAKTERISTIK KIMIA-SENSORI DAN STABILITAS POLIFENOL MINUMAN COKELAT-REMPAH - Puspita Sari; Eksi Utari; Yhulia Praptiningsih; Maryanto Maryanto (Faculty of Agricultural Technology, University of Jember, 2015)
Cacao bean and cocoa products contained flavonoid polyphenol compounds. Monomeric flavanols (catechin and epicatechin) are the major flavonoids in cocoa products that have high antioxidative properties. High antioxidant activity of cocoa made it potential to be developed into healthy drink by adding extract of spicy. The aims of this research were to characterize chemical-functional (polyphenol content and antioxidant activity), and sensory (hedonic) properties, and also polyphenol stability of spicy-chocolate beverage during storage. Spicy-chocolate beverage was made from ingredients of cocoa extract, spices extract (ginger, lemongrass, and sappanwood), and sugar. The results showed that the total polyphenol content and antioxidant activity of spicy-chocolate beverage decreased as the lower addition of cocoa extract and greater addition of the spicy extracts in beverage formulations. The sensory test showed that panelists preferred spicy-chocolate beverage formula P5 (75% of cocoa extract; 9% of sappanwood extract; 3% of lemongrass extract and 13% of ginger extract), containing the total polyphenol content of 80,77 mg/100 mL, antioxidant activity (percent inhibition) of 72,66%, and sensory (hedonic) scores of the color, aroma, taste, and overall attributes were 2,08; 1,92; 2,14 and 2,08, respectively. Spicy-chocolate beverages were stored at refrigeration temperature had polyphenol stability higher than beverage stored at room temperature.Keywords: spicy-chocolate beverage, polyphenol, antioxidant activity, polyphenol stability